2001
DOI: 10.1080/03079450120054604
|View full text |Cite
|
Sign up to set email alerts
|

The role of egg drop syndrome virus in acute respiratory disease of goslings

Abstract: An outbreak of severe acute respiratory disease characterized by tracheitis and bronchitis was observed in young goslings on a large-scale goose farm in Hungary. Histological examination revealed amphophilic intranuclear inclusion bodies in the superficial epithelial cells of the trachea and bronchi. Adenovirus-like particles were detected by electron microscopy, and the virus isolated from the trachea and the lungs was identified as egg drop syndrome (EDS) virus by serological and genomic examination. The cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…For transmission electron microscopic (EM) examination, ca. 3-mm 3 small pieces were cut from the liver and lung samples previously fixed in formaldehyde solution, and prepared as described elsewhere (Ivanics et al, 2001). …”
Section: Gross Pathology Histopathology and Electron Microscopymentioning
confidence: 99%
“…For transmission electron microscopic (EM) examination, ca. 3-mm 3 small pieces were cut from the liver and lung samples previously fixed in formaldehyde solution, and prepared as described elsewhere (Ivanics et al, 2001). …”
Section: Gross Pathology Histopathology and Electron Microscopymentioning
confidence: 99%
“…EDSV mainly causes sudden drop in egg production in laying birds accompanied by a reduction in egg quality. In 2001, a case was reported in young goslings with severe acute respiratory disease in Hungary, and the infectious agent was confirmed to be the EDSV by the viral isolation, serological and genomic examinations, and experimental infection of 1-day-old goslings (3). Cha et al (4) also found that EDSV caused severe acute respiratory symptoms in 10-day-old Pekin ducklings.…”
Section: Genome Announcementmentioning
confidence: 99%
“…6 Furthermore, DAdV-A has also been isolated from young goslings suffering from acute respiratory symptoms indicating that DAdV-A is also able to induce disease in geese. 11 In addition, quail were shown to become infected with DAdV-A and to develop classical signs of EDS-76. 5 The susceptibility of chickens to infection with DAdV-A is age independent.…”
Section: Introductionmentioning
confidence: 99%